Analysis of Readiness to Implement Private Entity Financial Accounting Standards at CV Al-Barokah Jaya Wonodadi Village, Wonodadi District, Blitar Regency - Ayu Khusnita; Novi Khoiriawati (PT Mattawang Mediatama Solution, 2023)
The purpose of this study was to determine the readiness of CV Al-Barokah Jaya, Wonodadi Village, Wonodadi District, Blitar Regency to implement Private Entity Financial Accounting Standards (SAK EP) and explain the obstacles encountered in the process. This research is qualitative research with a descriptive approach and uses primary data. Data were obtained using interviews and documentation and analyzed using the Miles and Huberman models. The results showed that the preparation of financial reports at CV Al-Barokah Jaya did not refer to Financial Accounting Standards. The financial statements consist of an income statement. The readiness of Human Resources, Finance, and Infrastructure shows that CV Al-Barokah Jaya is not ready to implement Private Entity Financial Accounting Standards. CV Al-Barokah Jaya experiences several obstacles in applying the Private Entity Financial Accounting Standards. Constraints from the readiness of human resources, namely a lack of understanding of accounting based on SAK EP, lack of experience in preparing financial reports based on SAK EP, have never attended training either on preparing financial statements or SAK and there is no socialization regarding SAK EP. Constraints from the readiness of the financial aspect, namely the financial statements that are made are only income statements and the preparation has not implemented SAK.